(untitled) - Segui, William T.; William T. Segui (Pacific Grove, CA)
This up-to-date book includes the latest specification from the American Institute of Steel Construction (AISC). The emphasis is on the design of building components in accordance with the provisions of the AISC Load and Resistance Factor Design (LRFD) Specification and the LRFD Manual of Steel Construction. Without requiring students to have a knowledge of stability theory or statically indeterminate structures, the book maintains a balance of background material with applications
Includes bibliographical references and index
Keywords: Building; Iron and steel; Load factor design; Steel; Structural